Determination Method of Retinoic Acid Using High Performance Liquid Chromatography and Application on the Whitening Night Cream - Aqnes Budiarti; Nila Vuqohan (Proceeding Of The International Seminar and Conference on Global Issues, 2016)
Retinoic acid is commonly used for bleaching facial in the whitening treatment. The concentration of retinoic acid in a topical preparation is 0.025 to 0.1% based on the cosmetics requirements so that it needs a validated determination method. The aims of this study were to validate the determination method of retinoic acid using HPLC and to apply the validated method on the whitening night cream. Determination of retinoic acid using a HPLC (Jasco PU-2080 plus) equipped with ultraviolet detector (2070 plus) at a wavelength of 340.3 nm. The stationary phase used C18 (12.5 cm x 4 mm) and the mobile phase used a mixture of methanol:water:glacial acetic acid (90:10:0.5, v/v/v), delivered with flow rate of 1.3 mL/min. The method was validated in parameter terms of precision, accuracy, linearity, sensitivity (LOD and LOQ) and selectivity. The applied samples were taken from beauty clinics in Semarang. The proposed method complied with the validity requirements. RSD value of precision test was 0.09%-0.37%, accuracy test resulted recovery value for sample A was 99.92%-100.78% and sample B was 99.44%-101.42%, good linearity with a correlation coefficient (r) = 0.9996, LOD and LOQ were 0.16 µg/mL and 0.54 µg/mL, respectively and the method had a good selectivity. Retinoic acid in sample A was 0.02% and sample B was 0.02%. The results showed that the concentration of retinoic acid in the samples were not excessive. Keywords: determination method, retinoic acid, whitening night cream, HPLC